Research Trends in Football Training for Young Players in the Last 15 Years: Bibliographic Analysis - Al Ardha, Muchamad Arif; Nurhasan; Sidik, Rizky Muhammad; O’Donnell, Dan; Hunter, Matt; Sujarwanto; Prianto, David Agus; Kusuma, I Dewa Made Aryananda Wijaya; Bikalawan, Sauqi Sawa; Putra, Kukuh Pambuka (Physical Education Theory and Methodology, 2023)
The objective of this paper is to evaluate the research trends in football training for young players under 18 years old in the last 15 years. Materials and methods. This was a bibliometric analysis and systematic review study. Articles published since 2008 were searched for by the keywords “Football Training” and “Football Exercise” using a comprehensive strategy on SCOPUS research journal databases. There were 1,053 articles with 4802 citations mined on October 17th, 2023. Thereafter, 217 articles were selected for further analysis by using VOS Viewer computer software. Results. The United Kingdom (67), The United States (60), and Spain (41) were the three countries that had the most publications in football training. There were 6 keyword clusters that reflected various research focuses on football training for younger players. Based on the top 10 most cited references in football training for younger players, there were several major themes that covered various aspects of the research trend and development in the last 15 years, i.e. (1) Factors in the Development of Young Football Players, (2) Tactical Analysis and Collective Behavior in Small-Sided Games, (3) Game Intensity and Activity Profile in Young Football Players, (4) Plyometric Training and Its Effects on Preadolescent Players, and (5) Injury Prevention and Neuromuscular Training in Adolescent Football Players. Conclusions. Football research for under-18 players has grown rapidly. This research trend shows that football requires not only physical and technical skills, but also social and mental aspects. Further research can be directed toward understanding and integrating holistic aspects of football coaching, including the development of non-physical skills, such as leadership, teamwork, and conflict resolution. Further investigation into the use of technology in football coaching, such as video analysis, sensor-based performance measurement, and artificial intelligence applications to provide deeper insight into player progress.